Tuning the reactivity of nanostructured indium tin oxide electrodes toward chemisorption. Issue 32 (23rd March 2015) - Forget, A.; Tucker, R. T.; Brett, M. J.; Limoges, B.; Balland, V.
Abstract : This contribution highlights correlation between the surface concentration of a chemisorbed organophosphorous probe (flavin mononucleotide) and the relative hydroxyl surface coverage of nanostructured ITO electrodes, which can be tuned during post-deposition reductive annealing. Abstract : This contribution highlights correlation between the surface concentration of a chemisorbed organophosphorous probe (flavin mononucleotide) and the relative hydroxyl surface coverage of nanostructured ITO electrodes, which can be tuned during post-deposition reductive annealing. The resulting modified electrodes are very stable in aqueous solution, highly hydrophilic and fully-accessible to the bulk solution.